Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1989
DOI: 10.1002/path.1711570209
|View full text |Cite
|
Sign up to set email alerts
|

Different types of segmental sclerosing glomerular lesions in six experimental models of proteinuria

Abstract: From 133 to 615 glomeruli were examined in sections of kidneys from each of 60 animals, representing six rodent models of proteinuria. Particular attention was paid to the position of segmental lesions. Lewis rats given sheep anti-rat glomerular basement membrane antibodies had lesions almost exclusively at the glomerulo-tubular junction. Wistar rats on a diet of 24 per cent casein or with subtotal nephrectomy and a diet of 24 per cent soya had lesions mainly at the hilum. Wistar rats given bovine serum albumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 21 publications
1
34
0
Order By: Relevance
“…Conditions that reduce total glomerular filtration surface are associated with progressive renal disease characterized by focal segmental glomerulosclerosis (Hostetter et al 1981) as observed in p53 transgenic mice. In addition, such changes have been seen in kidneys of adult rats subjected to reduction of renal mass (Howie et al 1989). Second, those nephrons that do develop in p53 transgenic kidneys may not be normal.…”
Section: Discussionmentioning
confidence: 99%
“…Conditions that reduce total glomerular filtration surface are associated with progressive renal disease characterized by focal segmental glomerulosclerosis (Hostetter et al 1981) as observed in p53 transgenic mice. In addition, such changes have been seen in kidneys of adult rats subjected to reduction of renal mass (Howie et al 1989). Second, those nephrons that do develop in p53 transgenic kidneys may not be normal.…”
Section: Discussionmentioning
confidence: 99%
“…Since progression of CRF is at least partially related to glomerular hyperfiltration [4], vegetable protein might, therefore, be more advantageous in the prevention of progression of CRF than animal protein. This is indeed suggested by several animal studies where, as compared with animal-based low-protein diets (APD), soya-based vegetable low-protein diets (VPD) are more effective in slowing the progression of CRF in normal [5] and in partially nephrectomised Wistar rats [5, 6, 7] and in normal Fischer rats [8, 9, 10]. …”
Section: Introductionmentioning
confidence: 88%
“…Glomerular sclerosis has been reported to be remarkable in the vicinity of vascular poles in some animal models [14, 15] and human pathology including hypertension [16, 17], diabetic nephropathy [18], and hyperfiltration [19]. Collagen III, originally extraglomerular component and known as substrate of Tg-2 [20], has been expressed in vascular poles in human diabetic nephropathy [21] and mesangial proliferative glomerulonephritis [22].…”
Section: Discussionmentioning
confidence: 99%